Real-World Experience with Venetoclax Treatment for Newly-Diagnosed Acute Myeloid Leukemia in Japan (VENUS Study): An Interim Analysis Focusing on Neutropenia Management - Tatsunori Goto; Hiroki Numata; Yuna Katsuoka; Nobuhiko Uoshima; Satoru Hara; Jun Ando; Shuichi Ota; Goichi Yoshimoto; Akihito Matsuoka; Hideyuki Hashiba; Tetsuo Morita; Atsuko Tsutsui; et al. (Oncology and Therapy)
Abstract Introduction Venetoclax has demonstrated clinical benefit for newly-diagnosed acute myeloid leukemia (AML), but significant neutropenia is a concern. Data on the time course of neutrophil counts for across treatment cycles in real-world settings remain limited. We report an interim analysis of the VENUS study, which examined neutropenia management in patients with AML receiving venetoclax with azacitidine (VEN/AZA) in Japan. Methods This multicenter (10 sites), retrospective, observational study included adults with newly-diagnosed AML ineligible for intensive chemotherapy and initiating venetoclax treatment. Treatment patterns, granulocyte colony-stimulating factor (G-CSF) use, antifungal prophylaxis, and time course of neutrophil counts were analyzed for patients who received > 1 cycle of venetoclax. Results Venetoclax was administered for a median 27.0 days in Cycle 1 and then a median 21.0 (range 14.0–22.0) days for subsequent cycles, with median dose holds at the end of each cycle of 8.5–15.0 days. Patients (n = 81) receiving G-CSF were treated with VEN/AZA for a median of 6.0 cycles versus 3.0 in those who did not receive G-CSF (n = 39). In Cycle 1, median neutrophil counts decreased to < 500/µl during Days 8–28 but recovered to > 500/µl by Days 29–35. Median nadir neutrophil count was reached during Days 22–28 in almost all subsequent cycles until Cycle 10. Neutrophil counts decreased to < 500/µl in some cycles but improved to > 500/µl by the next week, suggesting neutrophil levels without higher risk of infection in most patients after Cycle 2 with venetoclax dosing schedule modifications and G-CSF administration. Eighty-eight (73.3%) patients received antifungal prophylaxis, but risk-based antifungal prophylaxis may be considered. Conclusion This real-world analysis provides insight into the timing of neutrophil count recovery with dosing schedule modification of venetoclax and G-CSF use in patients with newly-diagnosed AML receiving VEN/AZA, informing timing of the use of antifungal prophylaxis for patients at higher risk.